Transformation of vocational skills for doormat craftsmen from persons with disabilities using assistive technology - Edy Purnomo; Bayu Rahmat Setiadi; Ishartiwi Ishartiwi; Eka Ary Wibawa; Angga Damayanto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
Vocational skills in an inclusive society are needed in business trips within an organization. The Mitra Sejahtera Center for Disability Empowerment (PPDMS) is an organization of persons with disabilities that is productive in producing patchwork mat products in quite a large capacity. This research wants to reveal how assistive technology in their business can change their vocational skills before and after knowing technology. This study uses a qualitative approach with a unique case of doormat crafts at PPDMS in Gunungkidul Regency. The research subject is the organizational chart, including the chairman and members involved in the production of doormats. The results of this study indicate that their vocational skills underwent a significant transformation after assistive technology was introduced. Before they learn assistive technology, their skill is to weave mats with the help of conventional looms. Developing more modernly, the use of mechanization with non-machine looms accessible for persons with disabilities has changed weaving skills to weaving skills complemented by skills in spinning threads. Developing even more rapidly, engineering technology-based vocational skills create job specifications for persons with disabilities. The users of these semi-automatic machines must be skilled and understand the machine mechanization system. This research implies that with the existence of assistive technology, the transformation of vocational skills goes hand in hand with developments in technology and science.